Autonomy of action among elderly women on physical activity programs in Brazil and Belgium: a comparative study - Paulo de Tarso Veras Farinatti; Bruno Ferreira da Costa Blois de Assis; Nádia Souza Lima da Silva (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n2p107 Autonomy of action is important for quality of life. This study compared the autonomy of action of elderly female participants on physical activity programs in Brazil (IMMA, n=47, age=75±5 years) and Belgium (ISEPK, n=77; age=69±7 years), using the Senior System for Evaluation of Autonomy of Action (SysSen). The SysSen is composed of a questionnaire (QSAP) about the aerobic power and upper limb strength needed for a life perceived as autonomous, and a fi eld test (TSMP), in which the subject walks 800 m carrying predetermined loads. The QSAP results are used to calculate an Index of Expressed Autonomy (IAE) and the TSMP to calculate an Index of Potential Autonomy (IAP). The ratio of IAP to IAE then gives an Index of Autonomy of Action (IAP/IAE=ISAC). An ISAC of 1.0 or more defi nes the subject as independent. IMMA and ISEPK data were compared with ANOVA for repeated measures or Friedman ANOVA, depending on distribution (p<.05). The results revealed that: a) the IAP was lower for women on the IMMA than for those on the ISEPK, whereas their needs in terms of physical activities (IAE) were similar; b) Most of the IMMA subjects had ISAC<1.0, in contrast with those on the ISEPK program; c) In both groups, the activities related to aerobic power made a greater contribution to the IAE than those depending on upper limb strength; d) All four parts of the QSAP made similar contributions to the IAE. In conclusion, the elderly women from IMMA had defi cits in autonomy of action, mainly as a result of insuffi cient physical fi tness for the declared demands of daily activities.